Lean manufacturing : - Feld, William M. (St. Lucie Press, 2001)
There are some very good books available that explain the Lean Manufacturing theory and touch on implementing its techniques. However, you cannot learn "how to be" lean from merely reading the theory. And to be successful in the real-work environment you need a clear comprehension of how lean techniques work, rather than just a remote understanding of what they are. You need to know what does and does not work in different situations. And you need the benefit of practical experience in their implementation.Lean Manufacturing: Tools, Techniques, and How to Use Them gives you the benef.